ANALISIS FIQH ISLAM TERHADAP TRANSAKSI JUAL BELI YANG DILARANG - Raja Ritonga; Putri Anisah Nasution; Rukiah Nst; Rina Riski; Maya Borotan; Arobiah Nasution (Izdihar: Jurnal Ekonomi Syariah, 2023)
Muamalah transactions in Islam can develop along with the progress of the times. However, transactions must be carried out while still referring to the propositions or rules that exist in Islamic teachings. Each transaction will have different legal impacts. This is by the contract used in the transaction when it takes place because the contract can be categorized as valid, fasid, or vanity. This article aims to discuss the analysis of Islamic fiqh related to muamalah buying and selling transactions which are prohibited in Islam. The research method used is a type of literature with an interpretive approach to the opinions of the fiqh madhhab scholars. The research data were taken from the results of reference searches sourced from the library, in the form of books, articles, and other scientific works. Furthermore, the data were analyzed with descriptive analytics. The results of the study show that transactions in muamalah sales and purchases that are prohibited can be categorized into three types. Namely, (1) transactions are prohibited because of expertise, (2) transactions are prohibited because they violate the principles of not being unjust and not being wronged and (3) transactions are prohibited because sighat is used.